The tomato gene Ty-6, encoding DNA polymerase delta subunit 1, confers broad resistance to Geminiviruses - Xuexue Shen; Upinder Gill; Marjon Arens; Zhe Yan; Yuling Bai; Samuel F. Hutton; Anne-Marie A. Wolters (Theoretical and Applied Genetics, 2025)
Key message The tomato Ty-6 gene conferring resistance against begomoviruses has been cloned and shown to be a variant of DNA polymerase delta subunit 1. Abstract Ty-6 is a major resistance gene of tomato that provides resistance against monopartite and bipartite begomoviruses. The locus was previously mapped on chromosome 10, and in this study, we fine-mapped Ty-6 to a region of 47 kb, including four annotated candidate genes. Via whole-genome resequencing of Ty-6 breeding lines and several susceptible breeding lines, the polymorphisms in gene sequences were discovered and gene-associated markers were developed for marker-assistant breeding. Further, virus-induced gene silencing and candidate gene overexpressing in susceptible tomatoes revealed that Ty-6- mediated resistance is controlled by Solyc10g081250, encoding the DNA polymerase delta subunit 1, SlPOLD1 . The single nucleotide polymorphism of Ty-6 results in an amino acid change that might influence the fidelity of virus DNA replication.

Mapping of the S. demissum late blight resistance gene R8 to a new locus on chromosome IX - Kwang-Ryong Jo; Marjon Arens; Tok-Yong Kim; Maarten A. Jongsma; Richard G. F. Visser; Evert Jacobsen; Jack H. Vossen (Theoretical and Applied Genetics, 2011)

A genome-wide genetic map of NB-LRR disease resistance loci in potato - Erin Bakker; Theo Borm; Pjotr Prins; Edwin van der Vossen; Gerda Uenk; Marjon Arens; Jan de Boer; Herman van Eck; Mariëlle Muskens; Jack Vossen; Gerard van der Linden; Roeland van Ham; et al. (Theoretical and Applied Genetics, 2011)